ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK DI KECAMATAN GATAK - Abellita Sherly Ramadhani; Maya Widyana Dewi; Rukmini Rukmini (CV. Denasya Smart Publisher, 2026)
This study aims to determine the effect of service quality, cost transparency, and officer competence on public satisfaction in Gatak District, Sukoharjo Regency. This study employed quantitative methods, collecting data through questionnaires distributed to 95 respondents, determined using the Slovin formula. Data analysis was performed using multiple linear regression using SPSS 23 software, including validity, reliability, classical assumption tests, F-tests, t-tests, and the coefficient of determination (R²). The results showed that all three independent variables had a positive and significant effect on public satisfaction. Meanwhile, the t-test results indicated that service quality, cost transparency, and officer competence each had a positive and significant effect on public satisfaction, thus all hypotheses in this study were accepted.